The health and fitness profiles of nurses in KwaZulu-Natal - R. Naidoo; Y. Coopoo (AOSIS, 2007)
Back pain has been recognized as a problem in hospitals, with up to 50% of healthcare staff reporting symptoms (Smedly, Egger, Cooper and Coggon, 1997 and Engels, van der Guilden, Senden and van 't Hof, 1996). The general purpose of this study was to determine the health and fitness profiles of nurses working in a public hospital. It was hypothesized that there is a correlation between the prevalence of lower back pain and being overweight or obese amongst nurses. One hundred and seven nurses from a local hospital in KwaZulu Natal participated in this study. Responses from a health questionnaire examining medical history, dietary, exercise and lifestyle patterns were analysed. Fitness tests determinedflexibility (sit and reach), muscular strength (back and grip strength), aerobic capacity (Astrand-Rhyming cycle) and anthropometrical data (percent body fat and BMI). Results suggested overall poor health and fitness profiles and a high incidence of back pain correlating with increased body fat percentages, thus accepting the hypothesis. The need for health and wellness intervention strategies in hospitals for the nurses was emphasized.